Perceptions of primary schools' headmasters and teachers towards the concepts, importance, and practices of school and family partnerships - Wee, Jennifer Beng Neo (1999)
The primary purpose of this study was to examine the headmasters' and teachers' perceptions towards the concepts, importance and practices of school and family partnerships. Specifically, this study examined their perceptions of the concepts of partnerships, their perceptions of the importance of parent involvement in the children's education, the school practices and the teachers' practices in contacting families. This study also sought to identify the partnership model adopted by Petaling primary schools, and the barriers faced by the schools in forging partnership. The relationship between the teachers' perceptions of the importance of parent involvement and the school practices in parent involvement were also examined. Proportionate stratified random sampling was used to select the subjects. A total of 553 respondents answered the questionnaires using a four-point Likert scale. Fourteen respondents randomly selected from two high-achieving schools were also interviewed for the in-depth study. Descriptive data were analysed in the form of frequencies, percentages, means, and standard deviations. Correlation techniques and t-test were also used in the analysis of the data. Qualitative interview data were analysed using open coding strategy. Overall, the findings showed that the respondents' perceptions of the concepts of partnerships were partial and confined to only school support activities and home learning activities. Majority of them perceived that parent involvement was important in the children's education, especially for the children's cognitive, emotional and social development. Only a few school practices were carried out, and home involvement practice was identified as the partnership model adopted by Petaling primary schools. Parents were perceived to be the primary barriers to school and family partnerships.